A Robust Multiple Ant Colony System for the Capacitated Vehicle Routing Problem - Toklu, N. E.; Montemanni, R.; Gambardella, L. M. (2013 IEEE International Conference on Systems, Man, and Cybernetics, 2013)
In transportation problems like the vehicle routing problem, the decision makers are increasingly adopting the idea that the problem data can be subject to uncertainty. The uncertainty can be encountered because of events that are not exactly predictable, like weather conditions, traffic jams, etc. In this paper, we study vehicle routing problem with uncertain travel costs. Then, to solve the problem, we propose a robust multiple ant colony system: a metaheuristic in which multiple ant colonies work in parallel to generate a collection of solutions with different levels of protection against the uncertainty. The uncertainty is handled by incorporating linear formulations from the field of robust optimization into the metaheuristic approach.